2019
DOI: 10.1530/edm-19-0090
|View full text |Cite
|
Sign up to set email alerts
|

Urinary steroid profiling in diagnostic evaluation of an unusual adrenal mass

Abstract: Summary Adrenal oncocytomas are rare tumours, with only approximately 160 cases reported in the literature. We report the use of urinary steroid profiling as part of their diagnostic evaluation and prognostication. A 45-year-old woman presented with clinical features of hyperandrogenism. Serum biochemistry confirmed androgen excess and computed tomography (CT) demonstrated a 3.2 cm adrenal tumour with density 39 HU pre-contrast. Urine steroid profiling showed elevated tetrahydro-11 deoxycortisol (THS), which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…This so-called heterogeneity of steroidogenesis observed is a reflection of immature and dedifferentiated cell features, which are the hallmark of ACC [11,13,[15][16][17]. To our knowledge, no serum or urinary steroid metabolites associated with prognostic factors in ACC have been demonstrated to date, but several papers have reported these were useful for the diagnosis of ACC [11][12][13][14][15][16][17][18][19]. Consistent with our recommendation, [17,18] were recommended.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This so-called heterogeneity of steroidogenesis observed is a reflection of immature and dedifferentiated cell features, which are the hallmark of ACC [11,13,[15][16][17]. To our knowledge, no serum or urinary steroid metabolites associated with prognostic factors in ACC have been demonstrated to date, but several papers have reported these were useful for the diagnosis of ACC [11][12][13][14][15][16][17][18][19]. Consistent with our recommendation, [17,18] were recommended.…”
Section: Discussionmentioning
confidence: 52%
“…Recently, steroid profiling has emerged as a powerful novel diagnostic tool for ACC [11][12][13][14]. Previous reports demonstrated that examination of serum steroid metabolites using liquid chromatography tandem mass spectrometry (LC-MS/MS) [12,13] or urine steroid metabolites using gas chromatography mass spectrometry (GC-MS) [15][16][17][18][19] are useful for distinguishing ACC from adrenocortical adenoma. Furthermore, the ENSAT recommends a biochemical workup for suspected ACC that includes serum cortisol, aldosterone, 17-hydroxyprogesterone, dehydroepiandrosterone sulfate (DHEAS), androstenedione, testosterone, and 17-beta-estradiol (http://www.ensat.org/page-1317312).…”
Section: Introductionmentioning
confidence: 99%
“…The observed heterogeneity of steroidogenesis re ects immature and dedifferentiated cell features, which are the hallmark of ACC [11,13,[16][17][18]. To our knowledge, no serum or urinary steroid metabolites associated with prognostic factors in ACC have been demonstrated to date, but several papers have reported these were useful for the diagnosis of ACC [11][12][13][14][15][16][17][18][19][20][21][22]. Consistent with our recommendation, Schweitzer et al reported that the combination of androgen precursor (17-hydroxypregnenolone, progesterone, and DHEA), mineralocorticoid precursor (11-deoxycorticosterone), glucocorticoid precursor (11-deoxycortisol), and sex hormone (DHEAS and estradiol) was useful for ACC diagnosis [13].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in non-androgen producing ACC, the differentiation between ACC and CPA becomes challenging because the end-product cortisol presents similarly between ACC and CPA. Previous reports demonstrated that serum steroid metabolite examination using liquid chromatography tandem mass spectrometry (LC-MS/MS) [12,13,15] or urine steroid metabolites using gas chromatography mass spectrometry (GC-MS) [16][17][18][19][20][21][22] are useful for distinguishing ACC from adrenocortical adenoma. Furthermore, the ENSAT recommends a biochemical workup for suspected ACC that includes serum cortisol, aldosterone, 17hydroxyprogesterone, dehydroepiandrosterone sulfate (DHEAS), androstenedione, testosterone, and 17-betaestradiol (http://www.ensat.org/page-1317312); however, feasible methods to detect or predict ACC behavior and prognosis aside from LC-MS/MS or GC-MS are limited by their lack of clinical availability.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, in non-androgen producing ACC, the differentiation between ACC and CPA becomes challenging because the endproduct cortisol presents similarly between ACC and CPA. Previous reports demonstrated that serum steroid metabolite examination using liquid chromatography tandem mass spectrometry (LC-MS/MS) [12,13,15] or urine steroid metabolites using gas chromatography mass spectrometry (GC-MS) [16][17][18][19][20][21][22] are useful for distinguishing ACC from adrenocortical adenoma. Furthermore, the ENSAT recommends a biochemical workup for suspected ACC that includes serum cortisol, aldosterone, 17hydroxyprogesterone, dehydroepiandrosterone sulfate (DHEAS), androstenedione, testosterone, and 17-beta-estradiol (http://www.ensat.org/page-1317312); however, feasible methods to detect or predict ACC behavior and prognosis aside from LC-MS/MS or GC-MS are limited by their lack of clinical availability.…”
Section: Introductionmentioning
confidence: 99%